Prospective of study of gestational diabetes mellitus risk in relation to maternal recreation physical activity before and after pregnancy - R. S., Sukesh; Rajmohan, Laxmy (International Journal of Research in Medical Sciences, 2018)
Background: Gestational diabetes mellitus is common complications of pregnancy. Physical activity is associated with a lower risk of type 2 diabetes mellitus. The present study aimed to know association between physical activity and gestational diabetes mellitus in the first 20 weeks of their pregnancy. Methods: In the current case-control study, 50 pregnant females with gestational diabetes mellitus as the case group and 50 pregnant females as control group were selected. To diagnose gestational diabetes mellitus using diagnostic criteria. Females with abnormal oral glucose challenge test (>140mg/dL) were asked to perform the three-hour 100 g oral glucose tolerance test. The details of physical activity were collected by pregnancy physical activity questionnaire. Anthropometric and other data were recorded for all of the participants. Results: Females with low total physical activity at early pregnancy were at a significantly higher risk of developing gestational diabetes mellitus compared to the ones with higher levels of physical activity. After adjusting for age, body mass index (BMI), gravidity and a family history of diabetes, females with low physical activity during 20 weeks of pregnancy were at a significantly higher risk of developing gestational diabetes mellitus. Females with the low intensity of sedentary, light and moderate physical activity are at a higher risk of developing gestational diabetes mellitus compared to females with a higher intensity of sedentary, light and moderate physical activity. Conclusions: Females should be encouraged to do regular daily physical activity during pregnancy, if there is no specific contraindication to it.